Associations Between Genetic Variants and Adverse Effects of Gefitinib in Non-small Cell Lung Cancer: A Systematic Review - Rangga Pradipa, Agya Marsaa; Al Ayyubi, Muhammad Shalahudin; Romadhona, Sabila (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2025)
Introduction: Lung cancer remains the leading cause of cancer-related death worldwide, with non–small cell lung cancer (NSCLC) accounting for approximately 85% of cases. Gefitinib is a tyrosine kinase inhibitor frequently used in NSCLC with favorable outcome. However, many patients develop severe adverse effects which might be influenced by genetic variability. Therefore, we aim to systematically review the gene variants and its association with adverse effects of gefitinib in NSCLC patients. Methods: A systematic search was conducted according to PRISMA guidelines across PubMed, Scopus, and Cochrane. Studies investigating the association between genetic variations with adverse effects following gefitinib in NSCLC were included. Extracted data encompassed study and patient characteristics, adverse effects, and identified gene variations. Risk of bias was assessed using the RoB-2 for randomized trials and Newcastle–Ottawa Quality Assessment Scale for cohort and case–control studies. Results: Nineteen studies involving 2.087 patients were included, with Japanese populations being the most studied. Polymorphisms in EGFR and ABCG2 were among the most studied genes. Rash, diarrhea, and hepatotoxicity are the most common adverse effects reported. Poor metabolizers of CYP2D6 and CYP3A53/3, and variations in ABCG2, ABCB1, and EGFR were associated with higher incidence of adverse effects. However, several studies demonstrated no associations between gene variations with adverse effects.  Conclusion: Genetic variations in ABCG2, ABCB1, CYP2D6, CYP3A53/3, and EGFR  may influence gefitinib-associated adverse effects, highlighting the need of pharmacogenomic testing to guide personalized treatment and improved patient safety. Keywords: Pharmacogenomics, Genetic Variants, Gefitinib, Non-Small Cell Lung Cancer, Adverse Effects